Comment on "Composition and origin of holotype Al‐Cu‐Zn minerals in relation to quasicrystals in the Khatyrka meteorite" by M. Ivanova et al. (2017). (25th June 2018) - Andronicos, C. L.; Bindi, L.; Distler, V. V.; Hollister, L. S.; Lin, C.; M Pherson, G. J.; Steinhardt, P. J.; Yudovskaya, M.
Abstract: Ivanova et al. (2017 ) proposed that the aluminides we described in the Khatyrka meteorite fragments, both crystal and quasicrystal metal phases, were derived from industrial materials used during placer gold mining and that these had been shredded and blast‐propelled into natural meteoritic material that happened to be at the site. The blast hypothesis was not supported by evidence that metal shrapnel or metal parts from mining operations (or from any other industrial use) occur at the site that are similar in composition to the aluminides that we described in Khatyrka; we doubt such compositions would exist because alloys with the compositions we reported have no known industrial applications. We further show that this hypothesis cannot be reconciled geologically, chemically, or physically with our observations. These observations demonstrate that the fragments central to our study have been embedded below gold‐bearing fluvial gravels in undisturbed sediment for at least 6670 to 8004 14 C years before mining operations commenced. The case presented here thus specifically rules out the blast hypothesis and also presents a challenge to other anthropogenic explanations. We also address each of Ivanova et al.'s points challenging our conclusion that the silicates attached to the aluminides were CV3 chondritic minerals.